Growth mechanisms of zinc oxide and zinc sulfide films by mist chemical vapor deposition. (28th December 2016) - Uno, Kazuyuki; Yamasaki, Yuichiro; Tanaka, Ichiro
Abstract: The growth mechanisms of zinc oxide and zinc sulfide films by mist chemical vapor deposition (mist-CVD) were experimentally investigated from the viewpoint of mist behaviors and chemical reactions. The proper growth model, either vaporization or the Leidenfrost model, was studied by supplying two kinds of mists with different kinds of sources, such as H2 16 O and H2 18 O for ZnO growth and ZnCl2 and thiourea for ZnS growth. Moreover, the origin of the oxygen atoms of ZnO was investigated using a quantitative analysis. The role of chloro complex of zinc in the growth of ZnS from aqueous solutions was also examined by systematic studies.